Argo : how the CIA and Hollywood pulled off the most audacious rescue in history - Mendez, Antonio J.; Baglio, Matt. (New York : Viking, 2012)
In 1979 Iranian militants stormed the American embassy in Tehran and captured dozens of American hostages; six Americans escaped. CIA agent Antonio Mendez devised a plan to rescue them. He and his team pretended to film a foreign movie in Iran in an attempt to rescue the six escaped Americans.
Includes bibliographical references (p. 309-310).
Keywords: Mendez, Antonio J; United States. -- Central Intelligence Agency; Iran Hostage Crisis, 1979-1981.; Diplomats -- United States -- History -- 20th century; Canada -- Foreign relations -- Iran; Iran -- Foreign relations -- Canada